The Effect of Javanese Language Educational Video on Compliance Blood Pressure Examination in Elderly People with A History of Hypertension at Posyandu Lansia Melati 5 Kepanjen Health Center Working Area - Friska Pricilia Wibowo; Ganif Djuwadi; Atti Yudiernawati (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Hypertension is the medical term for high blood pressure. Hypertension is commonly referred to as "The Silent Killer" because it shows no symptoms. Therefore, compliance to check blood pressure is important in controlling hypertension. Health education is needed to improve compliance, for example using educational videos in Javanese. Objective: This study aims to determine the effect of Javanese-language educational videos on compliance with blood pressure checks in elderly hypertension history at the Melati 5 Elderly Posyandu in the Kepanjen Health Center Working Area. Method: This type of research is quantitative with Pre-experimental research design using One Group Pre-Test Post-Test approach. The study population was all elderly people with a history of hypertension at Posyandu Melati 5 as many as 50 respondents, simple random sampling technique with a sample of 33 respondents. Result: The results showed that during the Pre-Test very few of the respondents were compliant (12%), while during the Post-Test almost all of the respondents were compliant (85%). Using the Wilcoxon test analysis with a p-value of 0.000 means that there is an effect of Javanese educational videos on respondent compliance. Conclusion: There is an effect of Javanese-language educational videos on compliance with blood pressure checks in elderly hypertension history at the Melati Elderly Posyandu 5 Kepanjen Health Center Working Area.